The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0122181
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Pocket-Sized Ultrasound Device Improves Physical Examination: Results of an In- and Outpatient Cohort Study

Abstract: BackgroundThe performance of pocket mobile ultrasound devices (PUDs) is comparable with that of standard ultrasonography, whereas the accuracy of a physical examination is often poor requiring further tests to assess diagnostic hypotheses. Adding the use of PUD to physical examination could lead to an incremental benefit.AimWe assessed whether the use of PUD in the context of physical examination can reduce the prescription of additional tests when used by physicians in different clinical settings.MethodsWe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 16 publications
2
54
0
1
Order By: Relevance
“…Ultrasonography used for examining the aorta or lungs, or for obstetric conditions had a higher diagnostic accuracy than ultrasonography used for heart or abdominal examinations. The quality estimate was higher in studies with focused abdominal POCUS scans (ie, scans limited to answering specific clinical questions, 32,51 such as whether ascites was present) than in studies entailing more explorative examinations. 47,57,58 Limited cardiac examinations 20,52 also had a higher quality estimate than more extensive examinations.…”
Section: Quality Of Scansmentioning
confidence: 97%
“…Ultrasonography used for examining the aorta or lungs, or for obstetric conditions had a higher diagnostic accuracy than ultrasonography used for heart or abdominal examinations. The quality estimate was higher in studies with focused abdominal POCUS scans (ie, scans limited to answering specific clinical questions, 32,51 such as whether ascites was present) than in studies entailing more explorative examinations. 47,57,58 Limited cardiac examinations 20,52 also had a higher quality estimate than more extensive examinations.…”
Section: Quality Of Scansmentioning
confidence: 97%
“…From an economical viewpoint, it is important to address the question whether expanded physical examination with the use of PSID could identify patients who require further testing. Colli et al . in their study involving 195 physicians who examined 1962 patients concluded that supplementing the physical examination with a brief assessment by means of PSID can reduce the need for further testing in various clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…The recent advent of handheld machines and smartphone probe attachments potentially allow for USS assessment as part of routine clinical examination. Colli et al demonstrated that the use of pocket USS in combination with clinical examination obviated the need for further testing in 95% of patients for whom there was a clinical question of pleural effusion [54]. Another pilot study demonstrated that use of pocket USS by a medical student could screen for the presence of left ventricular systolic dysfunction with a similar sensitivity and specificity to an experienced echocardiologist [55].…”
Section: Future Directionsmentioning
confidence: 99%